Analysis of surface ozone and nitrogen oxides at urban, semi-rural and rural sites in Istanbul, Turkey - TAYANÇ, METE (ELSEVIER, 2013)
Ozone (O-3) mixing ratios were measured at three different sites (urban/traffic, semi-rural and rural/island) in Istanbul from September 2007 to December 2009 in order to determine the diurnal, monthly and seasonal variations of O-3 and nitrogen oxides (NOx) and to study the local and regional impacts. This is the first study that evaluates the O-3 levels in semi-rural and rural sites in Istanbul in addition to the urban sites. The diurnal O-3 variations are generally characterized by afternoon maxima (64 ppb at the urban, 80 ppb at the semi-rural and 100 ppb at the rural site) and the nighttime minimum being more pronounced at the polluted urban site. The monthly mean O-3 mixing ratios start to increase in March, reaching their maximum values in August for the urban (similar to 25 ppb) and semi-rural sites (30 ppb). However, at the rural site, the monthly mean O-3 levels reach their maximum value in June (35 ppb). The O-3 mixing ratios for weekends were higher than those on weekdays at each site by up to 28%, possibly due to changes in VOC sensitivity and reduction in NO levels. In order to better understand and characterize the relationship between air masses and O-3 levels, cluster analysis was applied to the back-trajectories calculated by the HYSPLIT model for the semi-rural site. The analyses clearly showed that major transport is characterized by northern and western clusters, particularly from the Eastern Europe and the Mediterranean region, as well as recirculation over Istanbul due to high pressure systems leading to accumulated levels of O-3. The results clearly suggest that extended measurement networks from urban to rural sites should be considered for a more comprehensive evaluation of O-3 levels. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Istanbul; Surface ozone; Weekend effect; Cluster analysis; Urban; Rural; MAJOR PHOTOCHEMICAL POLLUTANTS; INTERACTION PATTERNS; BACKGROUND OZONE; AIR-POLLUTANTS; AREA; TRANSPORT; NOX; TRAJECTORIES; HYDROCARBONS; TEMPERATURE